Chapter Poggio Bracciolini's International Reputation and the Significance of Bryn Mawr, ms. 48 - Rundle, David (Atti, 2020)
Poggius Florentinus delighted in his local identity but he also, famously, had an international career, being in attendance at the Council of Constance, being resident in England for four years (1419-1422) and seeking employment at the imperial court. What is less recognized is how he sought for his literary works audiences far beyond his home-city and how some non-Italians were willingly collaborators in this creation of an international reputation. It has not been noticed before how a remarkable witness to this process is now housed in the Special Collections of Bryn Mawr. It, like other manuscripts in the library, reached its present location because of that twenty-century friend of Poggio and alumna of the college, Phyllis Goodhart Gordan. It now has the shelfmark ms. 48 and is a collection of Poggio's dialogues. What has not been recognized is that we can identify both its scribe and its illuminator and, by doing so, shed new light on Poggio's fortuna on the far side of Europe, in his one-time home of England.